Diffusion of Recapitulation Information System (SIREKAP) Innovation in Realizing the Integrity of the 2024 Elections in Meranti Islands Regency, Riau Province, Indonesia - Tinanto, Bherry; Zetra, Aidinil; Putera, Roni Ekha (JPSI (Journal of Public Sector Innovations), 2024)
This article discusses the diffusion of Recapitulation Information System (Sirekap) innovation to improve the integrity of the 2024 Election in Kepulauan Meranti Regency, Riau Province, Indonesia. The diffusion of innovation provides an overview of the extent to which the community accepts adopting the Sirekap Application. Integrity is a very important value in elections, so many developed countries utilize technology to improve the integrity of their elections. However, using technology not only improves election integrity but can also damage election integrity. The Indonesia General Election Commission (KPU) is trying to improve election integrity by using Sirekap to count and recapitulate votes in the 2024 election. Sirekap is a means of publishing vote counting and recapitulation tools. The use of Sirekap in the 2024 election has sparked debate among stakeholders at the national level. However, this incident did not occur in Kepulauan Meranti Regency without debate in the community. The purpose of this study is to analyze the efforts of the KPU of Kepulauan Meranti Regency, Riau Province Indonesian in communicating Sirekap technology to stakeholders and the social community and to analyze the assessment of stakeholders and the community regarding the existence of Sirekap. This research uses a case study method with triangulation techniques from interview data and documentation.  The study results show that the Sirekap Innovation Diffusion Process in the Meranti Islands Regency is running quite well by conveying innovations in supporting Sirekap. However, some innovations are not legally certain and prone to problems. The openness of public information and transparency of election result data are well established, thus realizing elections with integrity. Communication is carried out to all stakeholders except the community, even though the community is an important element in elections. User mastery of Sirekap technology is relatively fast. The social system that is formed is based on election organizers' sense of responsibility for the tasks that have been given. Election organizers, election supervisors, and election participants mostly responded well to the use of Sirekap in the Meranti Islands Regency. The community, as an element that is not directly involved with Sirekap, also gave a good response by actively accessing Sirekap on the 2024 Election results publication page so that Sirekap facilitates openness of information and transparency of election result data to realize elections with integrity.